2012
DOI: 10.1007/s00125-012-2476-6
|View full text |Cite
|
Sign up to set email alerts
|

Superior beta cell proliferation, function and gene expression in a subpopulation of rat islets identified by high blood perfusion

Abstract: Aims/hypothesis The blood perfusion of individual pancreatic islets is highly variable, with a subgroup of islets having high perfusion and blood vessels responsive to further blood flow increase induced by glucose. This study tested the hypothesis that there is heterogeneity between islets with regard to beta cell proliferation, function and gene expression based on differences in their blood perfusion. Methods Fluorescent microspheres were injected into the ascending aorta, and then microsphere-containing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 51 publications
8
38
0
Order By: Relevance
“…Another possible local effect is that islet blood flow is regulated by pregnancy-induced serotonin production. This merits further investigation as serotonin is known to have potent vasoconstricting effects [39] and because pancreatic islets are known to have a very high local blood flow that may underlie part of the functional heterogeneity between islets [40]. Previous studies of blood flow in islets of pregnant rats demonstrated that islet blood flow was increased at day 15 of pregnancy but decreased at day 18 of pregnancy [30].…”
Section: Local Effects Of Islet Serotoninmentioning
confidence: 99%
“…Another possible local effect is that islet blood flow is regulated by pregnancy-induced serotonin production. This merits further investigation as serotonin is known to have potent vasoconstricting effects [39] and because pancreatic islets are known to have a very high local blood flow that may underlie part of the functional heterogeneity between islets [40]. Previous studies of blood flow in islets of pregnant rats demonstrated that islet blood flow was increased at day 15 of pregnancy but decreased at day 18 of pregnancy [30].…”
Section: Local Effects Of Islet Serotoninmentioning
confidence: 99%
“…The present study shows that the previously described pool of highly functional, highly blood-perfused islets in the native pancreas [9] has a higher susceptibility to cellular stress with Microsphere-containing islets (c) regained a higher vascular density than non-microsphere-containing islets (b) post transplantation; insulin is shown in brown, endothelial cells in red; scale bar, 50 μm. Values are given as means ± SEM for six islet grafts of microsphere-or nonmicrosphere-containing islets, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…A low-oxygenated proportion of islets were found to be a resting or dormant population, which at increased metabolic demands could be activated and manifested as an increase in oxygen support [10]. Islets that in the native pancreas are highly blood-perfused were on the other hand observed to be the most functionally active, with higher glucose-stimulated insulin release, higher beta cell proliferation and a different gene expression in comparison with size-matched control islets [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this heterogeneity are unknown but this situation is reminiscent of the variability of placental lactogen-induced serotonin immunoreactivity in individual beta cells [26,27], and of the variability in glucose responsiveness of individual beta cells [28,29]. Heterogeneity of proliferation, gene expression and the function of beta cells between islets as a result of differential blood flow has also been documented in the rat [30]. It is possible that glycaemia is a direct regulator of CART…”
Section: Cart and Pancreatic Isletsmentioning
confidence: 99%